Draft Outline of the Fourth Five Year Plan State Government of Bihar - Planning Commission (Planning Commission, 1963)
This draft outline sets out the substance of the proposals of the state Government of Bihar for the Fourth Five Year Plan. The- final report will be prepared and published after the proposals contained in this draft' have been discussed with the Planning Commission and the representatives of the Central Ministries concerned. The preparation for the Fourth Plan started in 1963 when the State Government appointed a number of working groups consisting of senior administrators ,technical heads of departments, and economists.
State Government of Bihar